Predicting ligand-free cell attachment on next-generation cellulose−chitosan hydrogels - Johns, Marcus A.; Bae, Yongho; Guimaraes, Francisco E. G.; Lanzoni, Evandro M. [UNESP]; Costa, Carlos A. R.; Murray, Paul M.; Deneke, Christoph; Galembeck, Fernando; Scott, Janet L.; Sharma, Ram I. (American Chemical Society (ACS), 2018)
There is a growing appreciation that engineered biointerfaces can regulate cell behaviors, or functions. Most systems aim to mimic the cell-friendly extracellular matrix environment and incorporate protein ligands; however, the understanding of how a ligand-free system can achieve this is limited. Cell scaffold materials comprised of interfused chitosan−cellulose hydrogels promote cell attachment in ligand-free systems, and we demonstrate the role of cellulose molecular weight, MW, and chitosan content and MW in controlling material properties and thus regulating cell attachment. Semi-interpenetrating network (SIPN) gels, generated from cellulose/ionic liquid/cosolvent solutions, using chitosan solutions as phase inversion solvents, were stable and obviated the need for chemical coupling. Interface properties, including surface zeta-potential, dielectric constant, surface roughness, and shear modulus, were modified by varying the chitosan degree of polymerization and solution concentration, as well as the source of cellulose, creating a family of cellulose−chitosan SIPN materials. These features, in turn, affect cell attachment onto the hydrogels and the utility of this ligand-free approach is extended by forecasting cell attachment using regression modeling to isolate the effects of individual parameters in an initially complex system. We demonstrate that increasing the charge density, and/or shear modulus, of the hydrogel results in increased cell attachment.